Detection of NDM-1/5 and OXA-48 co-producing extensively drug-resistant hypervirulent Klebsiella pneumoniae in Northern Italy. (March 2022) - Lorenzin, Giovanni; Gona, Floriana; Battaglia, Simone; Spitaleri, Andrea; Saluzzo, Francesca; Trovato, Alberto; di Marco, Federico; Cichero, Paola; Biancardi, Anna; Nizzero, Paola; Castiglione, Barbara; Scarpellini, Paolo; et al.
Highlights: ST383, ST147 and ST15 hypervirulent Klebsiella pneumoniae clones were isolated in 2019 in Italy. Long- and short-read sequencing is needed for accurate plasmids characterisation. Hypervirulent STs harbouring multiple plasmids pose a great public-health challenge. ABSTRACT: Objectives: Using a hybrid long-read sequencing approach, we aimed to fully characterise four extensively-drug resistant (XDR) hypervirulent Klebsiella pneumoniae isolates, one of which represented the first strain isolated in Italy co-expressing NDM-1/5 and OXA-48 carbapenemases. Methods: Whole-genome sequencing was performed using Illumina and Oxford Nanopore Technology platforms. An assembly pipeline was used to recover the structures both of the chromosome and plasmids. Results: Multilocus sequence typing (MLST) showed that these strains belonged to high-risk sequence types (STs) not commonly circulating in Italy (ST383, ST147 and ST15). The hybrid sequencing approach allowed to characterise three multidrug resistance plasmids, which demonstrated high homology with previously sequenced plasmids, that were simultaneously detected in one ST383 strain carrying, respectively, bla NDM-1, bla NDM-5 and bla OXA-48 . Conclusion: This is the first report in Italy of new hypervirulent XDR K. pneumoniae clones characterised by co-production of OXA-48, NDM-1 and NDM-5. The discovery of new high-risk clones harbouring multiple mobile elements is a growing problem that poses a great challenge for public health.